Theater, Education and Politics: Freire and Boal perform at CEDECA Ceará (Revista Educação, Artes e Inclusão, 2022)
What do we mean when we talk about a theater teaching perspective, referenced in popular education, focused on the discussion of human rights? In this work, I reflect on the experience of creating a theater group with adolescents and young people, assisted by CEDECA Ceará, in a poor neighborhood of Fortaleza, in the year 2019, in addition to discussing the place of art in the educational and political performance of this institution and present the general lines of a theater teaching concept, from a dialogue between the theories of Paulo Freire and Augusto Boal. I worked as a community advisor and as education coordinator at CEDECA Ceará, and this work is the result of a critical reflection based on my participation, observation, interviews and reading of documents and texts published by the institution. I understand that the perspective of theater teaching, presented here, can inspire paths for a praxis of aesthetics, education and politics, whose objective is the respect and appreciation of the autonomy, dignity and identity of the subjects participating in the process.
Keywords: Theater teaching; popular education; human rights